2019
DOI: 10.7717/peerj.7628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes and molecular mechanisms in infant acute lymphoblastic leukemia withMLLgene rearrangement

Abstract: Infant acute lymphoblastic leukemia (ALL) with the mixed lineage leukemia (MLL) gene rearrangement (MLL-R) is considered a distinct leukemia from childhood or non-MLL-R infant ALL. To detect key genes and elucidate the molecular mechanisms ofMLL-R infant ALL, microarray expression data were downloaded from the Gene Expression Omnibus (GEO) database, and differentially expressed genes (DEGs) betweenMLL-R and non-MLL-R infant ALL were identified. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Drugs were identified through the Drug Gene Interaction Database (DGIdbv3.0.2;) for hub genes, which can serve as promising targets for GBM. , DGIdb is a user-friendly drug–gene interaction and the druggable genome data mining database, which mined the data from over 30 trusted sources such as ChEMBL, DrugBank, Ensembl, NCBI Entrez, PharmGKB, PubChem, clinical trial databases, and the literature in NCBI PubMed . Drugs were selected, which are supported by more than one database or have PUBMED references.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Drugs were identified through the Drug Gene Interaction Database (DGIdbv3.0.2;) for hub genes, which can serve as promising targets for GBM. , DGIdb is a user-friendly drug–gene interaction and the druggable genome data mining database, which mined the data from over 30 trusted sources such as ChEMBL, DrugBank, Ensembl, NCBI Entrez, PharmGKB, PubChem, clinical trial databases, and the literature in NCBI PubMed . Drugs were selected, which are supported by more than one database or have PUBMED references.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…By the end of gestation, it is probable that pre-malignant cells have colonized the BM. There is evidence that multiple first-hit mutations can change B cell adhesion/migration properties; for example, ETV6::RUNX1 is associated with a cell-intrinsic defect in CXCR4-CXCL12 signaling ( 35 ) and KMT2A -mutated BCP-ALL up-regulates protocadherin genes ( 36 ). An area of active interest is whether pre-leukemic cells can modify the BM niche prior to transformation; given the changes seen at the time of diagnosis (see below) this seems likely and novel experimental co-culture techniques will help in delineating these interactions.…”
Section: Subversion Of B-cell-microenvironmental Interactions Promote...mentioning
confidence: 99%
“…Moreover, gene expression studies that compared KMT2A -rearranged with non- KMT2A -rearranged infant ALL cases identified in KMT2A -rearranged samples the up-regulation of genes involved in homophilic cell adhesion (in particular protocadherin ( PCDH ) γ subfamily of genes). It has been assumed that the overexpression of these genes may cause different cell migration and invasion properties of KMT2A -rearranged cells [ 39 ].…”
Section: The Pre-leukemic Cell and Its Interaction With The Microenvironmentmentioning
confidence: 99%